Incidence of diseases in Japanese quail (Coturnix coturnix japonica) with special reference to bacterial and viral diseases in some selected areas of Bangladesh - Islam, Md Taimur; Talukder, Anup Kumar; Rahman, Md Ataur; Haider, Md Golam; Rahman, Abu Nasar Md Aminoor (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
Quail industry has become a promising sector in livestock of Bangladesh in last decade. This study was aimed to find out the incidence of bacterial and viral diseases in Japanese quail (Coturnix coturnix japonica) in Bangladesh. This is the first report about the incidences of diseases in Japanese quail in Bangladesh. The incidences of diseases were investigated by the clinical signs, gross lesions in different organs and histopathological changes of different tissues in bacterial and viral diseases. A total number of 476 birds, either diseased or dead, from 40 quail farms were included in this study. The result showed that the occurrence of viral and bacterial diseases in Japanese quail were 25.21% and 34.45%, respectively where as 15.13% cases were mixed infection. Newcastle disease was found as most prevalent (11.35%) among the viral diseases. On the other hand, colibacillosis was the highest prevalent disease accounting for 15.34% among all bacterial diseases. Moreover, 22.48% cases were other types of infections (mycoplasmosis, coccidiosis, aspergillosis, deficiency disorder and internal parasitic problem) and 2.73% cases were unidentified. The highest numbers of diseases were found in the age group 21 to 30 days (23.53%) whilst the quails aged between 11 to 40 days (59.67) were most vulnerable to various diseases. The highest occurrences of diseases were found in rainy season (39.29%). It can be concluded that Newcastle disease and colibacillosis are the most frequent challenge for the quail farming in Bangladesh. Strict bio-security and proper management system might effectively reduce the incidences of the reported diseases. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 410-418